Microscope for biological research in space - Tiensuu, Kiira (My University, 2020)
Understanding how space environment affects on biological systems has become especially important now, when manned space exploration missions beyond the low Earth orbit are under planning. Mini Fluorescence Microscope is European Space Agency's project with an objective to develop a breadboard model of a microscope that could advance radiation and gravity related biological research in space. A flight model of the microscope would be developed in the subsequent project. The purpose of this thesis is to investigate the potential of a miniaturized fluorescence microscope in space research. The thesis consists of three main topics. First, the purpose is to specify the fundamental questions in space biology that could be studied with microscopy approaches. Secondly, the state of the art in miniaturized microscopes and space microscopy are reviewed. Lastly, it is determined what are the potential platforms for this kind of instrument. Based on the review, applications for miniaturized fluorescence microscope in space research are diverse. The health threats for humans in space are more or less characterized, but the underlying cellular mechanisms are poorly understood and require more research. Studying the survivability of microorganisms would benefit space exploration in many ways, such as by supporting the further development of planetary protection policies. The smallest of the reviewed microscopes were not standalone instruments and the microscopes previously used in space were relatively large. There is a need for more independently functioning and compact space microscope. The potential platforms are facilities on-board the International Space Station, CubeSats and rovers.

Suunniteltaessa miehitettyjä avaruuslentoja Maan matalan kiertoradan ulkopuolelle, on yhä tärkeämpää ymmärtää miten avaruusympäristö vaikuttaa biologisiin systeemeihin. Mini Fluorescence Microscope on Euroopan avaruusjärjestön projekti, jonka tavoitteena on kehittää prototyyppi mikroskoopista, joka edistäisi säteilyyn ja painovoimaan liittyvää biologista tutkimusta avaruudessa. Lentomalli mikroskoopista kehitettäisiin seuraavassa projektissa. Tämän tutkielman tarkoituksena on selvittää mitä pienikokoisen fluoresenssimikroskoopin käyttö mahdollistaisi avaruustutkimuksessa. Tutkielma koostuu kolmesta pääkohdasta. Ensimmäiseksi määritellään ne avaruusbiologian peruskysymykset, joita voitaisiin tutkia mikroskopiamenetelmillä. Seuraavaksi tarkastellaan pienikokoisten mikroskooppien ja avaruusmikroskooppien teknisiä ratkaisuja. Lopuksi määritellään mitkä olisivat mahdollisia käyttöalustoja tällaiselle mittalaitteelle. Tutkielman johtopäätös on, että pienikokoisella fluoresenssimikroskoopilla on monipuolisia sovelluskohteita avaruustutkimuksessa. Avaruusympäristön ihmiselle aiheuttamat terveysuhat ovat jokseenkin määritelty, mutta niiden taustalla olevia solutason mekanismeja ymmärretään huonosti. Mikrobien selviytymisen tutkiminen avaruusympäristössä tukisi esimerkiksi planeettojen suojelupolitiikan kehittämistä. Pienimmät tarkastelluista olemassa olevista mikroskoopeista eivät olleet itsenäisesti toimivia laitteita, ja avaruudessa käytetyt mikroskoopit olivat puolestaan suhteellisen suurikokoisia. Itsenäisemmin toimivalle kompaktille avaruusmikroskoopille on siis tarvetta. Mahdollisia käyttöalustoja ovat kansainvälisen avaruusaseman laitteistot, CubeSatit ja mönkijät.
Keywords: space environment, radiation, microgravity, astrobiology, fluorescence microscopy, International Space Station, CubeSat, Mars rover